2009
DOI: 10.1088/1468-6996/10/2/025004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of starting powders on the sintering of nanostructured ZrO2ceramics by colloidal processing

Abstract: The effect of starting powders on the sintering of nanostructured tetragonal zirconia was evaluated. Suspensions were prepared with a concentration of 10 vol.% by mixing a bicomponent mixture of commercial powders (97 mol.% monoclinic zirconia with 3 mol.% yttria) and by dispersing commercially available tetragonal zirconia (3YTZ, Tosoh). The preparation of the slurry by bead-milling was optimized. Colloidal processing using 50 µm zirconia beads at 4000 rpm generated a fully deagglomerated suspension leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 43 publications
0
19
0
2
Order By: Relevance
“…Fully dense ceramics with uniform microstructure and fine grain size is essential to stabilize the tetragonal phase as well as to improve the mechanical properties such as hardness and toughness. There are many TSS profiles conducted to control the grain growth of Y-TZP ceramics [1,4,5,8,[24][25][26][27][28][29][30][31]61]. Only few researchers successfully obtained fully dense ceramics with controlled grain growth (<5 times of powder size) [1,4,5,25,28,29,31,62].…”
Section: Y-tzp Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fully dense ceramics with uniform microstructure and fine grain size is essential to stabilize the tetragonal phase as well as to improve the mechanical properties such as hardness and toughness. There are many TSS profiles conducted to control the grain growth of Y-TZP ceramics [1,4,5,8,[24][25][26][27][28][29][30][31]61]. Only few researchers successfully obtained fully dense ceramics with controlled grain growth (<5 times of powder size) [1,4,5,25,28,29,31,62].…”
Section: Y-tzp Ceramicsmentioning
confidence: 99%
“…Only few researchers successfully obtained fully dense ceramics with controlled grain growth (<5 times of powder size) [1,4,5,25,28,29,31,62]. Among these studies, Binner et al [31] and others [1,29] successfully sintered nanostructured zirconia ceramics. Binner et al [31] achieved fully dense (99% of TD) nanoceramics with the application of hybrid radiant and microwave sintering.…”
Section: Y-tzp Ceramicsmentioning
confidence: 99%
“…Kim et al ., 4 in the case of alumina sintered at 1150°C under an applied pressure of 80 MPa, obtained an in‐line transmittance of 47% at a wavelength of 640 nm. As SPS typically operates with punches and die in graphite, the maximum pressure in the SPS method is generally limited by the compressive strength of the material used for the dies, which is 140 MPa for high‐strength graphite 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…As SPS typically operates with punches and die in graphite, the maximum pressure in the SPS method is generally limited by the compressive strength of the material used for the dies, which is 140 MPa for high-strength graphite. [8][9][10] In 2006, Anselmi-Tamburini et al 11 reported a method for preparing dense functional oxide compacts with a crystallite size in the range of 10-20 nm. They used relatively short thermal cycles (o10 min) coupled with a progressive increase in pressure (up to 1 GPa) to promote a high degree of compaction and very limited grain growth.…”
Section: Introductionmentioning
confidence: 99%
“…Con respecto a esto, los polvos con dimensiones de partícula del orden de los nanómetros están en desventaja debido a la facilidad a aglomerarse que tienen los mismos. Esto conduce a que en el material final existan poros intra e inter aglomerados, siendo los primeros a nanoescala, mientras que los últimos están a nivel submicrónico o incluso del orden del micrón, en especial cuando los polvos se aglomeran en diferentes escalas (Kim y Han, 2004;Suárez et al, 2009b).…”
Section: Materiales Cerámicos Nanoestructuradosunclassified